2008
DOI: 10.1098/rspb.2008.1552
|View full text |Cite
|
Sign up to set email alerts
|

Extreme convergence in stick insect evolution: phylogenetic placement of the Lord Howe Island tree lobster

Abstract: The 'tree lobsters' are an enigmatic group of robust, ground-dwelling stick insects (order Phasmatodea) from the subfamily Eurycanthinae, distributed in New Guinea, New Caledonia and associated islands. Its most famous member is the Lord Howe Island stick insect Dryococelus australis (Montrouzier), which was believed to have become extinct but was rediscovered in 2001 and is considered to be one of the rarest insects in the world. To resolve the evolutionary position of Dryococelus, we constructed a phylogeny … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
214
6
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(251 citation statements)
references
References 32 publications
(69 reference statements)
25
214
6
6
Order By: Relevance
“…island 'stepping-stone') explanation is feasible (e.g. see Forster 1964;Buckley et al 2009). As for most animals and plants, dispersal can never be completely ruled out for the micropholcommatid taxa, but a further discussion on this hypothesis requires calibrated molecular data and a more rigorous understanding of micropholcommatid ecology.…”
Section: Biogeographymentioning
confidence: 99%
See 1 more Smart Citation
“…island 'stepping-stone') explanation is feasible (e.g. see Forster 1964;Buckley et al 2009). As for most animals and plants, dispersal can never be completely ruled out for the micropholcommatid taxa, but a further discussion on this hypothesis requires calibrated molecular data and a more rigorous understanding of micropholcommatid ecology.…”
Section: Biogeographymentioning
confidence: 99%
“…One of the problems with dispersal biogeography is that such hypotheses are rarely falsifi able (Sanmartin and Ronquist 2004) -taxa could of course, potentially, have travelled anywhere at any time -although with the advent of DNA sequencing, the molecular dating of clades is one way of approaching the dispersal-vicariance debate (e.g. see Buckley et al 2009). For the Micropholcommatidae, no molecular dating data are currently available, and preliminary observations on live micropholcommatid specimens suggest that these spiders are ecologically restricted and highly prone to desiccation (see Natural History, below), rendering long-distance dispersal across the Pacifi c Ocean unlikely.…”
Section: Biogeographymentioning
confidence: 99%
“…It would be highly interesting to get a deeper insight into the potential combined effect of these two factors for these predators, and to compare them with other highly cryptic insects, for instance Orthoptera sensu stricto or Phasmatodea. It has recently been shown that several Phasmatodea lineages evolved convergently into the charismatic and robust Eurycanthinae ecomorph (Buckley et al 2009). …”
Section: Homoplasymentioning
confidence: 99%
“…progression rule | speciation | priority effect | community assembly | radiation zone E volutionists are drawn to the study of island biotas for their unique species (1)(2)(3)(4)(5), as refuges of extant, "relict" organisms (6,7), and most famously, for their displays of adaptive radiation (8,9). Likewise, ecologists have long recognized the value of islands as microcosms of the processes of community assembly (10,11).…”
mentioning
confidence: 99%